Psychometric properties of Malay-translated version of “desire for drug questionnaire” among opioid dependents - A. F, Mohd Khairi; Kadir @ Shahar, Hayati (Community Health Society Malaysia, 2020)
Background: Drug craving is a subjective experience that can induce and reinforce individual to consume drugs. Desire for Drug Questionnaire (DDQ) is one of the screening tools used to measure drug craving severity in individuals with drug dependent. However, the original English version of DDQ has never been translated into Malay language nor validated in Malaysia. Thus, the objective of this study is to translate the DDQ questionnaire and to assess the psychometric properties of the translated Malay version of DDQ among opioid dependents. Methodology: DDQ was translated from English into Malay language by language experts using forward and backward translation methods. The questionnaire was then undergone assessment for its validity and reliability. Construct validity of the questionnaire was tested using exploratory principal components factor analysis while internal consistency of the questionnaire was tested using Cronbach’s alpha. Eigenvalue more than 1 was set to be the criteria for factor extraction. Result: A total of 55 Methadone Maintenance Treatment (MMT) male clients had participated in this study. For all the 14-items in the questionnaire, the factor loading values were from 0.434 to 0.958. The exploratory principal component factor analysis for DDQ delineates all 14-items into three factors with variance of 45.51%. The Cronbach’s alpha value was good with 0.86 for total score, 0.79 for factor 1, 0.81 for factor 2 and 0.75 for factor 3. Conclusion: Malay-translated version of DDQ questionnaires has good psychometric properties. The questionnaire could be considered as a reliable instrument for assessment of drug craving level in Malay-language speaking drug dependents.